The junction: transcending sociotechnical divides through youth space - Dowlath, Rahul (School of Architecture, Planning and Geomatics, 2018)
Infrastructure continues to perpetuate the effects of splintering urbanism in South African cities. Where apartheid planning policies such as the group areas act used infrastructure as a mechanism of social organisation, this design dissertation proposes using architecture as social infrastructure to transcend these sociotechnical divides. The concept of the sociotechnical denotes the synergy of a city's infrastructural systems and its social life. In this design dissertation this idea is explored at various scales: at the urban level, through a development strategy that spatialises unsafe public open land; at the architectural scale, through surface articulation and interfacing with urban infrastructure; and at the technical level, through building performance analysis and technical design development in support of architectural goals. The project uses a distributed programme that stretches across communities in order to socialise the existing urban infrastructure of a pedestrian bridge. By leveraging the social significance of a local football club, the project proposes a social programme around the idea of a football clubhouse as a programmatic anchor. In reacting to urban infrastructure, the idea of imageability and presence are important considerations. These concepts enable youth to positively engage with the architecture, and allows the building to convey its purpose and programmatic intent, thereby creating a strong social interface with its users. Sociotechnical architecture is considered as an urban armature that socialises and spatialises urban infrastructure. The architecture therefore seeks the minimal amount of fixity to support a variety of flexible events surrounding sports and recreation activities. This is achieved through a selection of robust materials used in horizontal surfaces of social purpose, and the combination of structure, materiality and geometry to create a series of vertical surfaces of social presence and architectural imageability. The result is a strategic arrangement of architectural interventions deployed across a large urban scheme. By distributing the architecture across urban infrastructure, the project connects two communities and presents an architectural response to splintering urbanism.